Green Materials and Manufacturing Processes - Guarino, Stefano; Tagliaferri, Flaviana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The green approach is no longer (and can no longer be) a goal of the future, but it is a concrete and practical necessity of the present. To take stock of new trends, this Special Issue lines up some recently developed green materials and remarkable progress and developments in manufacturing processes.